ANALISIS PENERAPAN CORPORATE SOCIAL RESPOSIBILITY (CSR) TERHADAP LABA BERSIH PERUSAHAAN PADA PT. SEMEN BATURAJA (PERSERO) Tbk PALEMBANG - Riyani Tridina Swari; Andri Eko Putra; Oktariansyah Oktariansyah (Journal of Management Small and Medium Enterprises (SMEs), 2022)
The purpose of this study is to determine the application of Corporate Social Responsibility (CSR) towards the company's net profit at PT. Semen Baturaja (Persero) Tbk Palembang. This research method is a qualitative method. The results of the analysis showed that PT. Semen Baturaja (Persero) Tbk Palembang had implemented the Corporate Social Resposibilty program from 2016 to 2020 that was quite good and in accordance with the direction of the Ministry of SOEs, the Corporate Social Resposibility (CSR) program at PT. Semen Baturaja (Persero) Tbk has been divided into several assistance sectors, namely natural disasters, education & training, health improvement, infrastructure, worship facilities and preservation. However, the company's net profit experienced a decline from 2016 to 2020. Keywords : Corporate Social Resposibility (CSR), Net profit, Semen Baturaja